The Vākyapadīya. with the commentary Prakīrṇakaprakāśa of Helārāja, son of Bhūtirāja - Bhartrhari (University of Travancore Sanskrit series, 1942)
Classical verse treatise, with 10th century commentary, on semantics and philosophy of the Pāṇini school in Sanskrit grammar.